Quality of life in rural areas: A topic for the Rural Development policy? - Brauer, René; Dymitrow, Mirek (Bulletin of Geography. Socio-economic Series, 2014)
Contemporary transformations of rural areas involve changes in land uses, economic perspectives, connectivity, livelihoods, but also in lifestyles, whereupon a traditional view of ’the rural’ and, consequently, of ’rural development’ no longer holds. Accordingly, EU’s 2007-2013 Rural Development policy (RDP) is one framework to incorporate aspects labelled as quality of life (QOL) alongside traditional rural tenets. With a new rendition of the RDP underway, this paper scopes the content and extent of the expired RDP regarding its incorporation of QOL, in order to better identify considerations for future policy making. Using novel methodology called topic modelling, a series of latent semantic structures within the RDP could be unravelled and re-interpreted via a dual categorization system based on RDP’s own view on QOL, and on definitions provided by independent research. Corroborated by other audits, the findings indicate a thematic overemphasis on agriculture, with the focus on QOL being largely insignificant. Such results point to a rationale different than the assumed one, at the same time reinforcing an outdated view of rurality in the face of the ostensibly fundamental turn towards viewing rural areas in a wider, more humanistic, perspective. This unexpected issue of underrepresentation is next addressed through three possible drivers: conceptual (lingering productionist view of the rural), ideological (capitalist prerogative preventing non-pecuniary values from entering policy) and material (institutional lock-ins incapable of accommodating significant deviations from an agricultural focus). The paper ends with a critical discussion and some reflections on the broader concept of rurality.